WHOSe Heritage: Classification of UNESCO World Heritage "Outstanding Universal Value" Documents with Smoothed Labels - Bai, Nan; Luo, Renqian; Nourian, Pirouz; Roders, Ana Pereira (EMNLP 2021, 2021)
The UNESCO World Heritage List (WHL) is to identify the exceptionally valuable cultural and natural heritage to be preserved for mankind as a whole. Evaluating and justifying the Outstanding Universal Value (OUV) of each nomination in WHL is essentially important for a property to be inscribed, and yet a complex task even for experts since the criteria are not mutually exclusive. Furthermore, manual annotation of heritage values, which is currently dominant in the field, is knowledge-demanding and time-consuming, impeding systematic analysis of such authoritative documents in terms of their implications on heritage management. This study applies state-of-the-art NLP models to build a classifier on a new real-world dataset containing official OUV justification statements, seeking an explainable, scalable, and less biased automation tool to facilitate the nomination, evaluation, and monitoring processes of World Heritage properties. Label smoothing is innovatively adapted to transform the task smoothly between multi-class and multi-label classification by adding prior inter-class relationship knowledge into the labels, improving the performance of most baselines. The study shows that the best models fine-tuned from BERT and ULMFiT can reach 94.3% top-3 accuracy, which is promising to be further developed and applied in heritage research and practice.